88.4k views
3 votes
Solve for x. 7 + 11x + 60 = -13 + 3x

User Bergey
by
5.2k points

1 Answer

5 votes

Answer:

x = -10

Explanation:

Step 1: Write equation

7 + 11x + 60 = -13 + 3x

Step 2: Solve for x

  1. Combine like terms: 11x + 67 = -13 + 3x
  2. Subtract 3x on both sides: 8x + 67 = -13
  3. Subtract 67 on both sides: 8x = -80
  4. Divide both sides by 8: x = -10

Step 3: Check

Plug in x to verify it's a solution.

7 + 11(-10) + 60 = -13 + 3(-10)

67 - 110 = -13 - 30

-43 = -43

User Olafur Tryggvason
by
5.0k points